ASSESSMENT OF PATIENT KNOWLEDGE WITH COMPLIANCE WITH AVF CARE IN HEMODIALYSIS PATIENTS - M, MADHUMITHA; S, SANTHOSHI; V, RAMNATH; KUMAR K, SENTHIL (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Background: Arteriovenous fistula (AVF) is the preferred vascular access for hemodialysis due to its durability and lower complication rates. However, inadequate patient knowledge and poor compliance with AVF care can lead to infections, thrombosis, and reduced access longevity. Objective: To assess the knowledge and compliance of hemodialysis patients regarding AVF care and to identify demographic and clinical factors influencing these outcomes. Methods: A cross-sectional descriptive study was conducted among 60 hemodialysis patients at Meenakshi Medical College Hospital, Tamil Nadu. Data were collected using a structured, interviewer-administered questionnaire covering socio-demographics, knowledge, and compliance practices. Statistical analysis was performed using SPSS v29, applying descriptive and inferential methods with p < 0.05 as significant. Results: Among the participants, 67% were male and the mean age was 51.95 ± 9.65 years. Hypertension (65%) and diabetes mellitus (22%) were the most common comorbidities. Knowledge about AVF care was observed in 67% of patients, while 82% demonstrated compliance with care practices. However, only 47% showed a positive attitude toward AVF care. Despite moderate knowledge, a notable gap between knowledge and consistent compliance was identified. Conclusion: The study highlights that while many hemodialysis patients possess basic knowledge of AVF care, gaps in compliance and attitude persist, potentially compromising vascular access outcomes. Structured and ongoing patient education, reinforced by healthcare providers and family support, is essential to improve AVF care practices and long-term dialysis outcomes.